Flood monitoring and alerting system - Azman, Luqman Hakim; Mohd Nawi, Prof. Dr. Nazri (Applied Information Technology And Computer Science, 2022)
Flash flood is one of the terrifying natural disasters that happen in Malaysia. There are many states in Malaysia that experienced flood every year such as Kelantan, Perlis, Kedah, Johor and Kuala Lumpur. Flash floods has been a nightmare to every citizen in Malaysia because when flood occur there will be casualties either from human or animal, assets destroyed, and shelter will get affected. The existing floods alerting system can trigger alarm when flood water level has reached dangerous level. However, only a few approaches that can alert the administrator. Flood Monitoring and Alerting System is proposed that can ease both citizens and involved authorities. The objectives for this project are to design a system that can do early detection on flash floods so citizens can evacuate and secure their assets. Moreover, the proposed system can calculate distance from water to sensor and it will prevent casualties and assets damaged. In addition, the proposed system can generate a warning message to system administrator via Telegram application. The proposed system is monitored by administrator and system technician of Jabatan Pengaliran Sungai (JPS). The proposed system is built using NodeMcu which integrated with web-based system that connect to database. The proposed system can provide system administrator with indicator of water distance can warn and alert citizens with LED light and warning message when flood water have reached dangerous level. It is hoped this proposed system will help citizens to evacuate before flood reached their residence and can avoid casualties and assets damaged.